METODE EXPERIENTIAL LEARNING DALAM PEMBELAJARAN KETERAMPILAN MENULIS DESKRIPTIF PADA MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR - Patmawati, Patmawati (Pedagogik Journal of Islamic Elementary School, 2018)
This study describes the effectiveness of the application of experiential learning methods in learning descriptive writing skills for PGSD students in Barru's study. The benefits of this study are to inform the effectiveness of experiential learning methods in descriptive writing. This type of research is the one group pretest-posttest design experiment. The research subjects were all PGSD students in the first registration period of 2014.1 totaling 35 people. Data collection techniques are observation and tests. Data analysis techniques are descriptive statistical analysis and t-test. The results showed that the results of the comparison of the average student value coefficient (t count) between the experimental class (X1) and the control class (X2) were obtained at 5 ? t tabe1 at a significant level of 95%, namely ?0.95 = 1.70. Therefore, the t count is greater than t table at a significant level of 95%, then the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. So, t-test statistics show that experiential learning methods are effectively used in learning descriptive writing skills in PGSD students teach Barra.